Superior strength–ductility combination in Al alloys via dislocation gradient structure. Issue 5 (4th May 2023) - Wang, Feng; Li, Yue; Chen, Xinren; Zhao, Huan; Yaqoob, Khurram; Du, Yong; Wang, Zhangwei; Song, Min
ABSTRACT: The precipitation hardening is widely applied to strengthen Al alloys. Here, we report an alternative way to achieve high-strength Al alloys via forming the dislocation gradient through pre-torsion. Remarkably, the gradient Al alloys exhibit a sharp increase in ultimate tensile strength up to 605 MPa yet nearly without reducing the uniform elongation, thereby outperforming their counterparts. The superior strength–ductility combination is ascribed to the excellent strengthening and strain hardening effects stemming from the substantial hetero-deformation-induced hardening in the coarse-grained gradient Al alloys. Our study thus paves a new way to improve the mechanical properties of Al alloys. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: The gradient distribution of dislocations significantly increases the strength of the Al alloy with the neglectable reduction in uniform elongation, which enables exceptional mechanical properties that outperform the peak-aged counterpart.